HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DENGAN HASIL AKURASI SERVIS BACKHAND TOPSPIN DALAM PERMAINAN TENIS MEJA PADA CLUB TENIS MEJA PERSATUAN TENIS MEJA MANDIRI PANDAU - Eli sitimeliana sitimeliana; Saripin '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The problem in this study originated from the observation that the author found in the field that researchers meet the deficiencies in the current serving topspin backhand is still a lack of flexibility of the wrist at the time of serving topspin backhand during a backhand topspin serve, resulting in accuracy results are less than the maximum service. The purpose of this research was to determine the relationship of flexibility wrist with a backhand topspin accuracy results serve communion table tennis club tennis table Pandau independent. The samples in this study is not complete, or do not cover the entire study population, but only a portion of the population alone. Researchers took a sampling technique focuses on purposive sampling technique. To can research data used to test wrist flexibility, and test services for servicing accuracy backhand topspin. Data were analyzed with a simple product moment correlation. Based on the analysis of data get by the correlation of X with Y for rarithmetic = 0,94˃rtable= 0.666. Because of all the relationships shown in data analysis is significant, it is thus Ha Ho accepted and rejected. Where the provisions of the correlation of a correlation of a variable with other variables determined from rarithmeticrtable.Keywords : Wristflexibility, AccuracyResultsServiceBackhandTopspin